Integrating the third way and third space approaches in a post-colonial world: marketing strategies for the business sustainability of community-based tourism enterprises in Vietnam. Issue 15 (2nd August 2020) - Ngo, Tramy; Lohmann, Gui; Hales, Rob
ABSTRACT: This study investigates the potential to integrate third way and third space approaches for marketing community-based tourism enterprises (CBTEs) in less-developed countries. The outcome of this integration is reflected in marketing strategies oriented towards the business sustainability of CBTEs in Vietnam. In particular, proposals on three aspects of CBTE marketing, including market segmentation, product design and development, and product communication and promotion, are illustrated. Through the proposed marketing strategies, the research contributes to CBT theory by showing that paradoxical CBT problem domains can be better addressed by integrating different ideological and developmental approaches. Additionally, the strategies provide evidence-based, practice-driven guidance for the extensively evaluated but insufficiently tackled marketing issues for CBTEs in Vietnam.